Income Portfolios in Rural Ethiopia and Tanzania: Choices and Constraints. - Dercon, S; Krishnan, P (1996)
The article analyses the different income portfolios of households using survey data front rural Ethiopia and rural Tanzania. It suggests that the different portfolios held by households cannot be explained by their behaviour towards risk as is usually suggested. It is better explained by differences in ability, location, and in access to credit. A logit analysis of households with different income portfolios, controlling for the effects of location, suggests that entry into high-return activities is determined by investment in particular skills or by access to capital.